(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The introduction of Central Bank Digital Currencies (CBDCs) as legal tender in various nations is something that several Central Banks around the world are planning in the near future. Similar intentions have been made public by the Reserve Bank of India (RBI), and an Indian CBDC can be expected soon. For any assessment of the impact, an evaluation of the potentials and difficulties brought on by the adoption of CBDCs is necessary. The current financial system is observing the entry of CBDC. The development of CBDC is accelerating the advancement of blockchain technology and virtual currencies with the support of Central Banks around the world. In this study, we examine the existing research on CBDC’s in different countries. This research paper is analysing the differences between India’s digital rupee and private Cryptocurrencies. Our current analysis can offer recommendations for the Introduction of Digital rupee in India.